PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH PADA SMP 1 LHOKNGA KECAMATAN LHOKNGA KABUPATEN ACEH BESAR - Herawati .; Murniati AR; Yusrizal . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: Academic supervision is a series of activities to help teachers to develop their ability in managing learning process in order to achieve the learning goals. This study aimed to find out the description of academic supervision implemented by principal in State Junior High School 1 Lhoknga. This study used qualitative approach with descriptive method. The subjects of this study were principal, vice principals, and teacher. The results of this study showed that: (1) the principal involved all school personnel in designing academic supervision program. The designing process was conducted at the beginning of school year and the program was applied for two semesters. (2) The principal’s strategies in implementing academic supervision were preparing academic supervision instrument, providing socialization about the program plans to all teachers, carrying out a direct academic supervision to all teachers, and delegating the supervisor’s responsibility to all vice principals and some senior teachers that have been supervised. (3) The principal conducted follow-up academic supervision by giving guidance and trainings or Teacher Education Consensus Points to unprofessional teachers. The follow-up included the follow-up program of academic supervision, learning situation and factors that influence the students’ achievement, and some improvement that should be done. (4) The obstacle factors were the teachers who were unable to attend the supervision because of the reason they were sick and asked permission to follow training, the teachers who were not ready when the supervision was conducted. Keywords: Academic Supervision and PrincipalAbstrak: Supervisi akademik merupakan serangkaian kegiatan membantu guru mengembangkan kemampuannya mengelola proses pembelajaran demi pencapaian tujuan pembelajaran. Penelitian ini bertujuan untuk memperoleh gambaran tentang bagaimanakah  kepala sekolah SMP 1 Lhoknga dalam melaksanakan supervisi akademik. Penelitian ini merupakan penelitian kualitatif, dengan metode deskriptif. Pengumpulan data dilakukan dengan mengadakan pengamatan (observasi), wawancara dan dokumentasi. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah dan dewan guru. Hasil penelitian menunjukkan bahwa: (1) kepala sekolah dalam menyusun program kerja supervisi akademik dengan melibatkan peran serta seluruh personel sekolah, penyusunan program supervisi dilakukan pada awal tahun ajaran untuk dua semester. (2) strategi kepala sekolah dalam melaksanakan implementasi supervisi akademik yaitu: mempersiapkan instrumen supervisi akademik, dengan dilakukan teknik yang secara individual dan kelompok baik secara langsung, tidak langsung maupun kolaboratif. (3) melaksanakan tindak lanjut supervisi akademik kepala sekolah dengan memberikan pembinaan, mengikuti kursus-kursus maupun MGMP kepada guru yang belum profesional. (4) faktor hambatan, guru yang berhalangan hadir waktu pelaksanaan supervisi yang disebabkan karena sakit, izin dan mengikuti pelatihan.Kata Kunci: Supervisi Akademik dan kepala sekolah